2020
DOI: 10.1088/1361-6382/ab8bb6
|View full text |Cite
|
Sign up to set email alerts
|

Constraining gravity with eccentric gravitational waves: projected upper bounds and model selection

Abstract: Gravitational waves allow us to test general relativity in the highly dynamical regime. While current observations have been consistent with waves emitted by quasi-circular binaries, eccentric binaries may also produce detectable signals in the near future with ground-and space-based detectors. We here explore how tests of general relativity scale with the orbital eccentricity of the source during the inspiral of compact objects up to e ∼ 0.8. We use a new, 3rd post-Newtonian-accurate, eccentric waveform model… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 49 publications
1
4
0
Order By: Relevance
“…1 therein). Similar non-trivial behavior of the constraint with increasing eccentricity was found by Moore & Yunes in [57], who studied constraints on Brans-Dicke theory and Enstein-dilaton-Gauss-Bonnet gravity. Using Markov-Chain Monte Carlo methods, Moore & Yunes found that the constraints are strongest for moderately eccentric systems with e ∼ 0.4, with the projected constraints being an order of magnitude better than current constraints with quasi-circular binaries.…”
Section: Tests Of General Relativitysupporting
confidence: 79%
“…1 therein). Similar non-trivial behavior of the constraint with increasing eccentricity was found by Moore & Yunes in [57], who studied constraints on Brans-Dicke theory and Enstein-dilaton-Gauss-Bonnet gravity. Using Markov-Chain Monte Carlo methods, Moore & Yunes found that the constraints are strongest for moderately eccentric systems with e ∼ 0.4, with the projected constraints being an order of magnitude better than current constraints with quasi-circular binaries.…”
Section: Tests Of General Relativitysupporting
confidence: 79%
“…Similar to Brans-Dicke and Einstein-dilaton-Gauss-Bonnet gravity, it is expected that including the eccentricity into the binary parameters enhances the distinguishment between DCS gravity and GR [187]. To show that, we numerically calculate the mismatch between the frequency-domain waveforms in DCS theory and GR.…”
Section: Jcap05(2024)073mentioning
confidence: 98%
“…[126,129,137], the observation of the BBH system without eccentricity can not give the physically meaningful constraint. However, similar to Brans-Dicke and Einstein-dilaton-Gauss-Bonnet gravity, it is expected that including the eccentricity into the binary parameters enhances the constraint on DCS effects [187]. Especially, for the eccentric BBH system formed dynamically in densely populated environments [83][84][85], the DCS modification from GR is enhanced.…”
Section: Jcap05(2024)073mentioning
confidence: 98%
“…As discussed in [76], the degeneracy between the eccentricity and ω BD may deteriorate the accuracy of ω BD for e 0.1, but for moderate and large eccentricities, the constraint on ω BD becomes stronger. Due to the large eccentricity, the covariances between non-GR and GR parameters are broken, and the constraints on non-GR effects become stronger than quasicircular constraints for large eccentric I/EMRIs [77]. The above results are based on the FIM method and simple waveform templates.…”
Section: Introductionmentioning
confidence: 98%
“…The extra energy loss in BD theory makes both the orbital dynamics and the GW waveform of a compact binary system different from those in GR [54][55][56][57][58][59][60], so BD theory can also be probed by the observations of GWs [61][62][63][64][65][66][67][68][69][70][71][72][73][74][75][76][77][78]. However, the orbital evolution and gravitational radiation from binary black holes (BBHs) are identical in GR and BD theory, so GW observations of BBHs are unable to distinguish BD theory from GR [46,54,70].…”
Section: Introductionmentioning
confidence: 99%